Biochar From Palm Kernel Shell and Its Application For CU2+ Sorption - Candra, I Nyoman; Sari, Irma; Abdullah, Rosazlin; Elvia, Rina; Handayani, Dewi (IJIS Edu : Indonesian Journal of Integrated Science Education, 2026)
Oil palm kernel shells (KS) are a byproduct of oil palm processing that often receives little attention and is treated as waste. Biochar has various applications for example as an adsorbent. This study aims to prepare and characterize biochar from KS and evaluate its effectiveness in adsorbing Cu2+. The biochar (BKS) was prepared by heating KS in a furnace at 500°C for three hours. The resulting material was sieved using a 50-mesh sieve to ensure uniformity. Characterization of BKS showed that it had a surface area of 319.9 m2 g-1, a total pore volume of 0.168 cm3 g-1, and an average pore size of 1.049 nm, classifying it as microporous. Analysis for its functional groups revealed the presence of functional groups with stretching vibrations corresponding to O-H (3400 cm-1), C-H (2920 cm-1), C=O (1700 cm-1), C=C (1432-1690 cm-1), and C-O (1000-1200 cm-1). SEM imaging displayed a clear porous structure with well-defined channels. Adsorption isotherm experiments demonstrated that Cu2+ adsorption data using BKS aligned better with the Freundlich isotherm model than with the Langmuir model. These findings indicate that BKS derived from KS is less effective for removing Cu2+ ions from water compared to other biochars.